Outcomes of patients with infection related to a ventricular assist device after heart transplantation. Issue 10 (17th September 2019) - Moayedi, Yasbanoo; Multani, Ashrit; Bunce, Paul E.; Henricksen, Erik; Lee, Roy; Yang, Wenjia; Gomez, Carlos A.; Garvert, Donn W.; Tremblay‐Gravel, Maxime; Duclos, Sebastien; Hiesinger, William; Ross, Heather J.; et al.
Abstract: Background: Despite significant advances in durable mechanical support survival, infectious complications remain the most common adverse event after ventricular assist device (VAD) implantation and the leading cause of early death after transplantation. In this study, we aim to describe our local infectious epidemiology and review short‐term survival and infectious incidence rates in the post‐transplantation period and assess risk factors for infectious episodes after transplantation. Methods: Retrospective single‐center study of all consecutive adult heart transplant patients from 2008 to 2017. Survival data were estimated and summarized using the Kaplan‐Meier method. We quantified and evaluated the difference in the incidence rate between patients with and without infection using a Fine‐Gray model. The outcome of interest is the time to first infection diagnosis with post‐transplant death as the competing event. Results: Among 278 heart transplant patients, 74 (26.5%) underwent LVAD implantation. Twenty‐one patients (28.3%) developed an infection while supported by an LVAD. When compared to patients supported by an LVAD without a preceding infection, BMI was significantly greater (31.2 vs 27.8 kg/m 2, P = .03). Median follow‐up post‐transplantation was 3.01 years. Significant risk factors for the competing risk regression for infection after heart transplantation include LVAD infection (HR 1.94, [95% CI] 1.11‐3.39, P = .020) and recipient COPD (HR 2.14, [95% CI] 1.39‐3.32, P = .001) when adjusted for recipient age, gender, hypertension, diabetes mellitus, and body mass index. Conclusions: Patients with LVAD‐related infection had a significantly increased risk of infectious complications after heart transplantation. Further research on the avoidance of induction agents and reduced maintenance immunosuppression in this patient population is warranted.